SISTEM INFORMASI PEMBAYARAN KONTRAK PEKERJAAN BERBASIS WEB PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUAPATEN KEPULAUAN ARU - Teguh Pradana; Mujid Benamen (SPIRIT, 2021)
Abstract: This job payment information system is designed to improve the document creation system and payment archive management in the finance department of the public works and spatial planning department of the Aru Regency which still does not have a soft archive or E-Archive. This application processes data related to capital expenditures such as 3rd party data, official work packages, while the output is several payment documents, namely Payment Orders (SPM), Payment Payment Certificates (SPP), payment receipts and monthly payment realization reports. The method used in the design is the waterfall method,Keywords: Information System, Contract Payment, PUPR Service, Spm